Role of Oral and Local therapy as well as Lifestyle Modification in the Management of Leucorrhoea - Rachana Gupta, Dr (International Journal of Pharmaceutical & Biological Archive, 2015)
Role of Oral and Local therapy as well as Lifestyle Modification in the Management of Leucorrhoea